Revitalisasi Program Kawasan Rumah Pangan Lestari (Krpl) Berbasis Masyarakat di Nagari Panti Selatan Kabupaten Pasaman: Revitalization of the Community-Based Sustainable Food House Area Program (KRPL) in Nagari Panti Selatan, Pasaman Regency - Didi Al Amin; Melinda Noer; Devi Analia (IPB University, 2026)
The Sustainable Food House Area (KRPL) program is one of the government's strategies to strengthen household food security through sustainable and community-based utilization of home yards. However, its implementation in various regions still faces challenges, particularly in terms of sustainability and community participation after program support declines. This study aims to evaluate the implementation of the KRPL program in Nagari Panti Selatan, Pasaman Regency, and to formulate a community-based revitalization model to enhance its sustainability. This research employs a descriptive qualitative approach using the CIPP (Context, Input, Process, Product) evaluation model and Logical Framework Analysis (LFA). Data were collected through in-depth interviews, observations, Focus Group Discussions (FGD), and document analysis. The results indicate that the implementation of the KRPL program has not been optimal, as reflected in the low level of group independence, declining community participation, and suboptimal utilization of program support facilities. Stakeholder analysis reveals an imbalance in roles and influence among actors, with the Women Farmer Groups (KWT) as the main implementers having high interest but limited influence in program decision-making. Based on the LFA, the root causes are dependency on external assistance, weak institutional capacity, and insufficient integration of the program into village development policies. Program revitalization is necessary through strengthening group institutions, increasing the intensity of assistance, implementing continuous monitoring and evaluation, integrating the program into village development, and developing economic-oriented activities from yard utilization. The proposed community-based revitalization model emphasizes the importance of stakeholder synergy in improving the effectiveness and sustainability of the program. This study contributes to the development of community empowerment models to support sustainable household food security. Program Kawasan Rumah Pangan Lestari (KRPL) merupakan salah satu strategi pemerintah dalam memperkuat ketahanan pangan rumah tangga melalui pemanfaatan pekarangan secara berkelanjutan dan berbasis masyarakat. Implementasi program di berbagai daerah masih menghadapi tantangan, terutama terkait keberlanjutan dan partisipasi masyarakat setelah dukungan program berkurang. Tujuan penelitian ini untuk mengevaluasi pelaksanaan program KRPL di Nagari Panti Selatan, serta merumuskan model revitalisasi berbasis masyarakat yang dapat mendukung keberlanjutan program. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode evaluasi program melalui pendekatan CIPP (Context, Input, Process, Product) dan Logical Framework Analysis (LFA). Data dikumpulkan melalui wawancara, observasi, Focus Group Discussion (FGD), dan studi dokumentasi. Hasil penelitian menunjukkan bahwa pelaksanaan KRPL belum optimal, ditandai dengan rendahnya kemandirian kelompok, menurunnya partisipasi masyarakat, serta belum optimalnya pemanfaatan sarana pendukung program. Analisis stakeholder menunjukkan adanya ketimpangan peran dan pengaruh antar aktor, dengan KWT sebagai pelaksana utama yang memiliki kepentingan tinggi namun pengaruh terbatas dalam pengambilan keputusan program. Berdasarkan analisis LFA, akar permasalahan utama adalah ketergantungan terhadap bantuan eksternal, lemahnya kapasitas kelembagaan, dan kurangnya integrasi program dalam kebijakan pembangunan nagari. Revitalisasi program diperlukan melalui penguatan kelembagaan kelompok, peningkatan intensitas pendampingan, pelaksanaan monitoring dan evaluasi secara berkelanjutan, integrasi program dengan pembangunan nagari, serta pengembangan orientasi ekonomi dari pemanfaatan pekarangan. Model revitalisasi berbasis masyarakat yang dihasilkan menekankan pentingnya sinergi antar pemangku kepentingan dalam meningkatkan efektivitas dan keberlanjutan program. Penelitian ini memberikan kontribusi dalam pengembangan model pemberdayaan masyarakat untuk mendukung ketahanan pangan rumah tangga secara berkelanjutan.